TINJAUAN TEOLOGIS TERHADAP PANDANGAN GEREJA KATOLIK TENTANG KERAJAAN ALLAH DAN IMPLIKASINYA BAGI GEREJA MASA KINI - Adi Putra; Filmon Berek (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
This research is about theological study of the views of the Roman Catholic Church on the concept of the Kingdom of God which is equated with the Church. By using qualitative research, especially literature review, several errors were found in this concept. First, it is a mistake to equate the Church with the Kingdom of God as understood by the Roman Catholic group. Second, I strongly agree when I say that the Church is the government of Christ. It should be noted, however, that in the context of God's kingdom (note the OT and NT concepts previously discussed) God's reign includes all of creation and the universe. So that the KR group has narrowed the scope of God's government in the Kingdom of God if it only thinks that the scope of God's government is only within the scope of the church. Third, it concerns the hierarchy of salvation and the Pope as the representative of Christ, where in the context of the kingdom of God on earth, the Pope is the highest representative. Once again this view is too exaggerated and forced. Thus, it can be concluded that it is a big mistake to equate the Kingdom of God with the Church.